A assistência estudantil e a permanência das estudantes-mães na UNIFAL- MG - Figueiredo, Raquel Ferreira De (2019)
This paper deals with the student assistance policy and the conditions to the mother students in the university remain in the undergraduate study, in the context of the expansion of higher education. Starting in 2003, Brazilian federal universities underwent a process of restructuring and expansion, which allowed previously excluded student to have access to higher education, a fact that made the student population more heterogeneous. This context has expanded the possibilities of access for women, including those who are mothers and who reconcile student life with the exercise of motherhood. However, entry into higher education doesn't guarantee a student to remain and complete the undergraduate course. Thus, student assistance was institutionalized in federal universities, through Federal Decree No. 7234 in 2010 that provides for the National Program of Student Assistance (PNAES), as a public policy that aims to support the conditions for students to remain and complete higher education, as well as contributing to the reduction of social and regional inequalities. Studies on student permanence indicate that there are two types of permanence, both material and symbolic (ZAGO, 2006 and SANTOS 2009). However, the permanence of the mother student also involves other necessities that are related to the care of the children and the family life (URPIA, 2009; ÁVILA, 2010 and SANTOS, 2014). Thus, this study presents as a unit of analysis the conditions for the students who are beneficiaries of day care assistance at the Federal University of Alfenas (UNIFAL-MG) to complete their undergraduate program, since we understand that the permanence of these women in the university is peculiar once that they are in situations of socioeconomic vulnerability and have children who are still in early childhood, a phase that requires more care and assistance from the mother. Understanding how the current conditions of permanence i of the beneficiary students of childcare assistance in UNIFAL-MG interfere in their academic course is the purpose of this study. The documentary and empirical research, with a quantitative and descriptive approach, was performed through institutional data and a questionnaire applied to the 51 mothers students who constitute the study population. The data on the socioeconomic and academic profile of the students surveyed revealed that most of them come from public schools, entered the quota system (for public schools, economic profile or ethnicity), are enrolled in night classes and belong to low income families. Despite all the difficulty in reconciling motherhood, family life, domestic work and studies, most of them have a satisfactory Academic Performance Coefficient (CDA). We also verified that the institutional support of the University is reduced to a few actions of student assistance, which are geared much more towards the material permanence than the symbolic one. However, student assistance plays a key role in the material permanence of the student mothers, but it is not enough. Data on the symbolic permanence suggest that this type of permanence is a more vulnerable point and the least developed when considering the conditions of permanence of the mother students in UNIFAL-MG. Family support is the most accessed by those surveyed to be able to attend university space and especially to attend classes. The research results indicate that there are challenges to the student assistance policy and also to the university when thinking about the conditions of permanence of the mother students in the institution and points to the need for the development of pedagogical and infrastructure actions with the objective to make university space more welcoming to the presence of students with children.